First description of leaf-mining Nepticulidae and Tischeriidae (Insecta, Lepidoptera) feeding on the Chilean endemic plant genus Podanthus Lag. (Asteraceae) - Stonis, Jonas R.; Diškus, Arūnas; Remeikis, Andrius; Torres, Nixon Cumbicus (Zootaxa, 2016)
Despite taxonomic and conservation interest in the Chilean endemic plant genus Podanthus Lag. (Asteraceae: subfamily Asteroideae, tribe Heliantheae), no Podanthus-feeding Nepticulidae or Tischeriidae have ever been recorded. Here, on the basis of material reared from Podanthus from central Mediterranean Chile, we present the description of Stigmella podanthae sp. nov. (Nepticulidae) and a re-description of Astrotischeria chilei Puplesis & Diškus, 2003. Females and host-plant of the latter species were previously unknown. Both treated species are illustrated with numerous photographs of the leaf-mines, adults of both sexes, and male and female genitalia.